2021
DOI: 10.1021/acs.jpca.1c02384
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Methane Activation Mediated by Free Tantalum Cluster Cations: Size-by-Size Reactivity

Abstract: The energetics of small cationic tantalum clusters and their gas-phase adsorption and dehydrogenation reaction pathways with methane are investigated with ion-trap experiments and spindensity-functional-theory calculations. Ta n + clusters are exposed to methane under multicollision conditions in a cryogenic ring electrode ion-trap. The cluster size affects the reaction efficiency and the number of consecutively dehydrogenated methane molecules. Small clusters (n = 1−4) dehydrogenate CH 4 and concurrently elim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…It must be stressed that only the inclusion of both coupling reactions in the reaction sequence is capable to replicate the experimental data. The other reactions, such as the consecutive dehydrogenation of four methane molecules and the deoxygenation of two molecules of CO 2 , are consistent with previous experiments on the reaction of tantalum cations with methane and carbon dioxide [11b,19] …”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…It must be stressed that only the inclusion of both coupling reactions in the reaction sequence is capable to replicate the experimental data. The other reactions, such as the consecutive dehydrogenation of four methane molecules and the deoxygenation of two molecules of CO 2 , are consistent with previous experiments on the reaction of tantalum cations with methane and carbon dioxide [11b,19] …”
Section: Resultssupporting
confidence: 89%
“…As the low ion abundance of bare Ta 2 + and Ta 3 + (see Figure S3) impedes the study of their products from methane dehydrogenation, the only remaining cluster that facilitates this reaction with this hydrocarbon is Ta 4 + [11b] . In the reaction of the size‐selected [Ta 4 CH 2 ] + with CO 2 , several species are detected in the mass spectra, as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While gas phase ions containing noble metals have good activity toward coupling of CH 4 molecules, researchers have also paid attention to ions containing non‐noble metals to find active species exhibiting comparable performance with noble metal systems. The reactions of positively charged bare tantalum clusters Ta n + ( n =1‐10) and oxygen deficient Ta n O m + ( m =1 and 2) clusters with CH 4 have been systematically investigated by a cryogenic ring electrode ion trap [12k,35,45,52] . It was found that the Ta 8 O 2 + cluster has the ability to catalyze the C−C coupling of two CH 4 to generate C 2 H 6 [35] .…”
Section: Coupling Reactions Of Ch4 Moleculesmentioning
confidence: 99%